Effect of mullite synthesis methods on the spark plasma sintering behaviour and mechanical properties. (1st August 2016) - Rajaei, Hosein; Mobasherpour, Iman; Farvizi, Mohammad; Zakeri, Mohammad
Abstract : To understand the role of mullite powder synthesis method on the microstructural aspects and mechanical properties of the consolidated samples, this powder was prepared with two methods including sol–gel technique and direct reaction of alumina and kaolin (A–K mullite). The microstructural studies showed that the particle size of mullite powders synthesised with sol–gel method is lower than the mullite prepared from direct reaction. The spark plasma sintering (SPS) method was used for the consolidation of the samples. The scanning electron microscopy/energy‐dispersive X‐ray analysis showed that the samples prepared from sol–gel powder after the SPS process contain lower porosity and better compositional homogeneity compared with A–K mullite sample consolidated in a similar condition. The bending and hardness (H) tests results confirmed the better performance of sol–gel samples which is attributed to its lower porosity and better microstructural homogeneity.